Retrospective comparative study of surgical treatment of patients with fractures of the posterior acetabular wall - Prudnikov, Yurii; Klimovitsky, Volodymyr; Bondarenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Background: The development of the new minimally invasive and less traumatic approaches for the treatment of acetabular fractures is a priority direction of modern orthopaedics. Objective: to compare the results of surgical treatment of patients with fractures of the posterior acetabular wall by using KocherLangenbeck approach and a new minimally invasive approach. Material and methods: A retrospective comparative study of the results of treatment of 72 patients with the posterior acetabular wall fractures was conducted. A control group of 38 patients were treated with traditional Kocher-Langenbeck approach, the main group of 34 patients were treated with new minimally invasive surgical approach to the acetabulum. A complex assessment of the treatment results was performed with the evaluation of bioelectrical activity of the lower limbs muscles by electromyography, and evaluation the peripheral circulation by rheovasography, the functional state of the hip after surgical treatment was assessed according to Harris Hip Score, and the amount of postoperative complications within 8 and 12 months after surgical treatment was accounted. Results: The proposed minimally invasive approach has a less negative influence to the functional activity to the pelvic muscles (m. gluteus maximus and m.quadriceps femoris) than traditional Kocher-Langenbeck approach in one year after surgery. According to rheovasography data we noticed a faster recovery of peripheral circulation in patients of the main group compared to the control one. Functional state of the hip joint by Harris Hip score in 1 year after surgery averaged in the main group (86.6 ± 15.9) points and (65.2 ± 20.4) in the control group. Complications occurred in 50% in the main group against 71% in the control. Conclusion: the obtained data allowed us to recommend a new developed minimally invasive approach for the treatment of posterior acetabular wall fractures.